What on Warth Am I Here For? - Warren, Rick (USA, 2002)
This book will help you understand why you are alive and God's amazing plan for you-both here and now, and for eternity. Rick Warren will guide you through a personal 40-day spiritual journey that will transform your answer to life's most important question: What on earth am I here for? Knowing God's purpose for creating you will reduce your stress, focus your energy, simplify your decisions, give meaning to your life, and, most importantly, prepare you for eternity.
Keywords: Christian Life; Non-Fiction; Religion; Spirituality